A decision support system for DC optimal power flow analysis on large scale interconnected system - Santos, Elma P.; Azevedo, Anibal T. [UNESP]; Filho, Secundino Soares; Meira, Paulo César M.; Da Silva Filho, Donato (My University, 2011)
This paper proposes a decision support system for the National Interconnected System in Brazil. The developed decision support system is a tool that uses a DC optimal power flow to obtain the operating status of the network and enable the solution analysis for various problems, such as economic dispatch, sensitivity analysis of generation and transmission, expansion planning of generation and transmission.
Keywords: DC optimal power flow; Decision support system electric